Everett Strait Hughes papers - Hughes, Everett Strait, 1885-1957.
Correspondence, diaries, and orders concerning Hughes's career in the U.S. Army. Documents his service during the Mexican Punitive Expedition, 1916; World War II chiefly with the U.S. Army American Expeditionary Forces in France; and World War II in the European and North African theaters of operation. Pertains primarily to ordnance and general staff work. Also documents his years at the United States Military Academy, West Point, N.Y.
Correspondents include Levin Hicks Campbell, Mark W. Clark, John W. Coffey, Dwight D. Eisenhower, Curtis Franklin, Charles Barry Goodspeed, C. Ralph Huebner, Bob P. Hughes, Bob W. Hughes, W.F. Hughes, Geoffrey Keyes, H.R. Kutz, Robert McGowan Littlejohn, John Porter Lucas, Frank McCullough, George Van Horn Mosely, Beatrice Banning Ayer Patton, George S. Patton, Virgil L. Peterson, George Rogers, Woodrow Wilson Storey, and the Hughes family.
Army officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Campbell, Levin Hicks, -- 1886- -- Correspondence; Clark, Mark W. -- 1896-1984 -- Correspondence; Coffey, John W. -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Franklin, Curtis -- Correspondence; Goodspeed, Charles Barry -- Correspondence; Huebner, C. Ralph -- Correspondence; Hughes, Bob P. -- Correspondence; Hughes, Bob W. -- Correspondence; Hughes, W. F. -- Correspondence; Keyes, Geoffrey, -- 1888-1967 -- Correspondence; Kutz, H. R. -- Correspondence; Littlejohn, Robert McGowan, -- 1890-1982 -- Correspondence; Lucas, John Porter, -- 1890-1949 -- Correspondence; McCullough, Frank -- Correspondence; Moseley, George Van Horn, -- 1874-1960 -- Correspondence; Patton, Beatrice Banning Ayer, -- 1886-1953 -- Correspondence; Patton, George S. -- 1885-1945 -- Correspondence; Peterson, Virgil L. -- Correspondence; Rogers, George -- Correspondence; Storey, Woodrow Wilson -- Correspondence; Hughes family -- Correspondence; United States. -- Army -- Ordnance and ordnance stores; United States. -- Army -- History -- Punitive Expedition into Mexico, 1916.; United States. -- Army. -- American Expeditionary Forces; United States. -- Department of the Army. -- General Staff; United States Military Academy; Universities and colleges -- New York -- West Point; World War, 1914-1918 -- France; World War, 1939-1945 -- Africa, North; World War, 1939-1945 -- Europe; Army officers